Generalized Projective Synchronization for Different Hyperchaotic Dynamical Systems - M. M. El-Dessoky; E. Saleh (Discrete Dynamics in Nature and Society)
Projective synchronization and generalized projective synchronization have recently been observed in the coupled hyperchaotic systems. In this paper a generalized projective synchronization technique is applied in the hyperchaotic Lorenz system and the hyperchaotic Lü. The sufficient conditions for achieving projective synchronization of two different hyperchaotic systems are derived. Numerical simulations are used to verify the effectiveness of the proposed synchronization techniques.